Efeito de diferentes manejos sobre o escoamento superficial em microbacias experimentais no semiárido tropical - Araújo Neto, José Ribeiro de (2012)
On natural rainfall with similar characteristics in relation to total depth, duration and intensity, catchments with ephemeral runoff in semiarid regions, may or not present hydrological responses differentiated as a result of human intervention. The aim of this study was to investigate the anthropogenic influence on the hydrological responses of catchmentof ephemeral runoff in Caatinga biome, as well as generate information of the key hydrological variables involved in the rainfall-runoff and investigate the runoff of these catchments through the hydrological model CN-NCRS. The data were analyzed concerning the rainy seasons of the years 2009, 2010, 2011 and 2012. We monitored the hydrology of three catchments, in the first one vegetal cover was kept unchanged, in the second one vegetal cover was thinnedfor forage yield and the third one was applied the management of vegetation cutting/burning and planteda grass (Andropogongayanus, Kunt). The results present that the vegetation management influences the generation of runoff in the catchments reflecting on the number of rainfall events generators of runoff, total runoff, runoff peak, and the values of CN (curve number) calibrated and validated. 198 events were detected with rain in the watershed during the study period, and of these, 75 events generated runoff for the watershed with native vegetation which produced an average annual runoff coefficient of 9.0%, since the watershed with vegetation thinned 62 events generated runoff and the runoff coefficient average annual 5.6%. The lesser runoff for the watershed with vegetation thinned regarding to that with vegetation unchanged, suggests appropriate management for the production of forage in the semiarid zones, since it produces forage and reduces water losses by runoff. The practice of vegetation cutting/burning associated with grasses made the soil more exposed, allowing larger runoff events. The values of CN were calibrated and validated: 75.4 for the watershed with native vegetation; 72.3 for the watershed with vegetation thinned and 88.5 with watershed management with cutting / burning and planting pasture. Both the calibration and validation models showed good Nash and Sutcliffe coefficients higher than 0.6, as well as confidence indices of good to very good.. The CN calibrated and validated may be used to estimate runoff in similar conditions of management in the semiarid Brazilian Caatinga. The model CN-NRCS presented greater sensitivity to changes in the values of CN than to changes in the ratio λ. The CN-NCRS model presented low reliability, because of the temporal variation of the parameters and its high sensitivity of the input parameters (CN and λ), as well as the uncertainties in the input variable precipitation.